Construction Project Delay Risk Assessment Based on 4M1E Framework and Afghanistan Situation - Hijratullah Sharifzada; Yu Deming (Salehan Institute of Higher Education, 2024)
In the realm of construction project management, delays present a significant impediment, particularly within complex socio-political contexts such as Afghanistan. This study endeavors to elucidate the multifaceted nature of construction project delays in Afghanistan, employing the 4M1E (Man, Machine, Material, Method, and Environment) framework to conduct a comprehensive risk assessment. The research methodology entailed the development of a structured questionnaire grounded in an extensive review of pertinent literature, targeting 30 recognized causes of project delays. This instrument was administered to a representative sample of 144 professionals across the Afghan construction industry spectrum, including clients, consultants, and contractors. Analytical rigor was applied through the deployment of frequency, severity, and importance indices to evaluate the collected data. This analysis culminated in the distillation of ten paramount delay risk factors, encapsulating elements such as governmental policy stability modifications in project scope and design alongside delays in material testing and approval processes. A comparative dimension was incorporated to benchmark these findings against global standards, thereby enhancing the robustness of the study’s conclusions. Moreover, the research delineates the congruence and discordance among different respondent cohorts, bolstering the integrity of the identified delay factors through a validation of internal consistency and reliability. The strategic application of the 4M1E framework, contextualized within the Afghan construction landscape, furnishes pivotal insights for stakeholders, equipping them with a nuanced understanding necessary for the proactive mitigation of delay risks. The implications of this study are far-reaching, promising to augment project completion efficiency, budget adherence, and overall project success, with particular resonance for environments paralleling the intricacies of Afghanistan. Doi: 10.28991/CEJ-2024-010-01-06 Full Text: PDF